2008
DOI: 10.1136/bmj.39553.670231.25
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to prescribed antihypertensive drug treatments: longitudinal study of electronically compiled dosing histories

Abstract: Objective To describe characteristics of dosing history in patients prescribed a once a day antihypertensive medication. Design Longitudinal database study. Setting Clinical studies archived in database for [1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006]. Participants Patients who participated in the studies whose dosing histories were available through electronic monitoring. Main outcome measures Persistence with prescribed antihypertensive treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
606
7
21

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 758 publications
(679 citation statements)
references
References 32 publications
26
606
7
21
Order By: Relevance
“…Previously, monitoring of adherence using electronic devices has been found to provide benefits in the management of patients with resistant hypertension 11. Notably, just the announcement of monitoring adherence resulted in significant improvement of BP 12. Although this approach can be used as a therapeutic tool, it distorts the true adherence rates in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, monitoring of adherence using electronic devices has been found to provide benefits in the management of patients with resistant hypertension 11. Notably, just the announcement of monitoring adherence resulted in significant improvement of BP 12. Although this approach can be used as a therapeutic tool, it distorts the true adherence rates in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials in which adherence is assessed by pill‐counting adherence rates ≥80% are accepted as complete adherence to medication 1, 11. Electronic methods of adherence monitoring (ie, computerized records of pharmacy prescription or electronic monitoring of pill box opening) may be considered reliable alternatives, but it remains subject to the patient's behavior whether the removed pills are indeed ingested 1, 12, 13. Recently, toxicological urine analysis of the compounds or their metabolites has gained increasing interest 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…4 Thus, antihypertensive treatment that provides sustained BP-lowering efficacy beyond the 24-h dosing interval is of considerable clinical importance. This study shows that the direct renin inhibitor aliskiren 300 mg provides significant reductions from baseline in 24-h ambulatory BP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, approximately 18% of patients missed on average at least a single dose each week, and 50% missed at least one dose each month. 4 These findings indicate a clear need for antihypertensive treatments that provide sustained BP reductions beyond the 24-h dosing interval.…”
Section: Introductionmentioning
confidence: 96%
“…This could be attributed to the reasons why majority of discharged patients with diabetes often return to the hospital within a short time, either for same diabetes crisis, comorbidities or for related complications. An empirical finding showed that there are increased rates of re‐admission among patients with diabetes associated with poor medication adherence after discharge and emphasized on the need to involve the clients on personal discussion on their health condition and why they need to improve their level of participation in their care (Sharma, Kalra, Dhasmana, & Basera, 2014). There are possibilities that these patients do not have enough knowledge about the complications that could arise from poor management or refusal in taking treatment as prescribed.…”
Section: Introductionmentioning
confidence: 99%